Modified Particle Swarm Optimization for Blind Deconvolution and Identification of Multichannel FIR Filters. (23rd February 2010) - Khanagha Khanagha, Vahid Vahid; Khanagha Khanagha, Ali Ali; Tabataba Vakili Tabataba Vakili, Vahid Vahid
Abstract : Blind identification of MIMO FIR systems has widely received attentions in various fields of wireless data communications. Here, we use Particle Swarm Optimization (PSO) as the update mechanism of the well-known inverse filtering approach and we show its good performance compared to original method. Specially, the proposed method is shown to be more robust against lower SNR scenarios or in cases with smaller lengths of available data records. Also, a modified version of PSO is presented which further improves the robustness and preciseness of PSO algorithm. However the most important promise of the modified version is its drastically faster convergence compared to standard implementation of PSO.